Is Radical Surgery Alone Enough in T1-3N1a Colon Cancer? - Xu, Guoxiong; Jin, Yiqi; Fang, Changwen; Yu, Jingfan; Zhang, Zhixuan; Sun, Chunrong (Frontiers in Oncology, 2020)
Background: Low lymphatic tumor burden is associated with a better prognosis. However, it is uncertain whether those patients diagnosed as cN0 found to be pN+ could be a favorable subgroup in stage III disease. Radical surgery alone might avoid overtreatment in those patients. Methods: Eligible patients diagnosed with colon cancer without metastasis were recruited from the Surveillance, Epidemiology, and End Results (SEER) database from 2004 to 2016 using SEER*Stat 8.3.5 software (Surveillance Research Program, National Cancer Institute) and divided into two groups: surgery group (n = 3,081) and surgery followed by adjuvant chemotherapy group (n = 4,591). Overall survival (OS) and cause-specific survival (CSS) differences were assessed by Kaplan–Meier analysis, and survival differences were estimated with log-rank tests. Univariate and multivariate Cox proportional hazard regressions were used to assess hazard ratios (HRs) and 95% confidence intervals (CIs) for colon cancer patients. Results: A total of 7,672 pT1-3N1a colon cancer patients were recruited from 208,751 colon cancer patients. The 5-year CSS rates of patients without and with adjuvant chemotherapy were 80.0 and 90.7%, respectively. The receipt of adjuvant chemotherapy after the radical resection of the primary tumor was independently associated with 57.3% decreased risk of colon cancer-specific mortality compared with surgery alone (HR = 0.427, 95% CI = 0.370–0.492, P < 0.001, using surgery alone as the reference). Conclusions: Adjuvant chemotherapy was significantly associated with improved prognosis and radical surgery alone did not provide enough treatment for colon cancer with very low lymphatic tumor burden.